Sennoside A inhibits quorum sensing system to attenuate its regulated virulence and pathogenicity via targeting LasR in Pseudomonas aeruginosa - Han, Xiaofeng; Nan, Mengyue; Cai, Xinyu; Qiao, Boling; Chen, Lin; Shen, Lixin (Frontiers in Microbiology, 2022)
Pseudomonas aeruginosa is an important opportunistic pathogen, and the increased drug resistance has greatly increased the treating difficulty of the infection. Quorum sensing (QS) system is a cell density-dependent gene regulatory system, not only regulating the virulence of P. aeruginosa but also associating with the development of its drug resistance. Screening for agents targeting QS that inhibit bacterial virulence is considered a promising strategy to combat P. aeruginosa infections. In the present study, sennoside A, an isolated anthraquinone compound from rhubarb, has been found to be able to inhibit the expression of QS system in subinhibitory concentrations in P. aeruginosa. The expression of the QS-regulated virulence genes, including protease coding gene of lasA, elastase coding gene of lasB, rhamnolipid coding genes of rhlA as well as pyocyanin coding genes of phzA1, could also be inhibited by sennoside A in subinhibitory concentrations both in transcriptional and translational levels. Biofilms formation and the motility of twitching, swimming and swarming, which is respectively responsible for chronic infection and associated with the initial acute infection and chronic infections of P. aeruginosa are inhibited by sennoside A in a dose manner. The pathogenicity of Pseudomonas aeruginosa could be attenuated significantly by sennoside A evaluating by Chinese cabbage, Drosophila melanogaster and Caenorhabditis elegans infection models analysis. Sennoside A might target las system, mainly by LasR but LasI not excluded, to interfere QS and attenuate the pathogenicity of P. aeruginosa. It might also be a potential QSIs for other Gram-negative bacterial which need further research.